VISITATION RATE, EFFECTIVENESS AND EFFICIENCY OF POLLINATORS TO CADABA FRUITICOSA (LINN) DRUCE - G.MEERABAI (The Bioscan, 2012)
Abundance and flower visitation rate of the pollinators of Cadaba fruiticosa (Linn) Druce (Capparidaceae), a butterfly pollinated shrub was studied over a 3-year period. The objective was to elucidate interspecific differences in the “quantity” component of the plant-pollinator interaction. The plant was solely visited by three butterfly species of the family Pieridae. These 3 pollinator species differed in flower visitation rate (0.046 – 0.113 flowers/ min). This variation was explained by differences in flower handling time (HT) i.e. TF/NF. Though the proboscis length of Colotis eucharis and C.danae were equal (17mm), the HT was differed. Anapheis aurota had longer proboscis (20mm) than the other two species and HT were also high. The total no. of visits that each pollinator contributed to the plant (NFV) was estimated as the product of abundance and visitation rate. The results revealed that C.eucharis was more effective pollinator to C.fruiticosa and the pollinator effectiveness influenced by foraging behavior.